EEG event related potentials in sustained, focused and divided attention tasks: Potential biomarkers for cognitive impairment in HIV patients. Issue 2 (February 2021) - Meghdadi, Amir H.; Berka, Chris; Richard, Christian; Rupp, Greg; Smith, Stephanie; Stevanović Karić, Marija; McShea, Kevin; Sones, Emily; Marinković, Ksenija; Marcotte, Thomas
Highlights: Neurophysiological measures of attention differentiated individuals with HIV from healthy controls. HIV ERPs showed increased amplitude of P200 and decreased amplitude of the late positive potential. The increase in P200 amplitude was positively correlated with duration of HIV infection. Abstract: Objectives: The objective of this study was to assess the usability of event-related-potentials (ERPs) during sustained, focused, and divided attention tasks as biomarkers for cognitive decline in HIV patients. Methods: EEG was acquired using a mobile/wireless 9-channel system in 39 persons with HIV, with well-controlled immune function and 63 healthy control participants (HCs) during three ERP tasks: sustained attention, focused attention, and divided attention. Results: The HIV-group evidenced smaller late positive potential (LPP) and larger P200 amplitudes across the tasks compared to the HC group. P200 amplitude was correlated (r = 0.56) with the estimated duration of infection. Both groups showed higher P200 and LPP amplitudes in response to infrequent stimuli; this effect was not significantly different between groups. In the sustained attention task, the HIV-group showed significantly slower reaction time than controls while maintaining the same level of accuracy. In the divided attention task, the HIV-group showed a trend towards faster/less accurate responses. Conclusions: HIV seropositive participants receiving anti-retroviral treatment (ART) demonstrated significantly larger P200 amplitude during three different attention tasks. This may reflect attentional deficits characterized by over-attending to non-target/distracting stimuli. Significance: These findings demonstrate the potential benefits of EEG-ERP metrics derived from attention tasks as neurocognitive biomarkers for HIV. This approach may reveal underlying causes of attentional deficits in HIV patients.